Language proficiency modulates the engagement of cognitive control areas in multilinguals - Abutalebi, Jubin; Della Rosa, Pasquale A.; Ding, Guosheng; Weekes, Brendan; Costa, Albert; Green, David W. (Cortex, 2013)
Language proficiency should modulate the regions involved in language control in predictable ways during language switching. However, prior studies reveal inconsistent effects on the regions involved in language monitoring [pre-Supplementary Motor Area/Anterior Cingulate Cortex (pre-SMA/ACC)] and language selection (left caudate) conceivably because variations in relative proficiency are confounded with other between-group differences. We circumvented this problem in an fMRI (functional Magnetic Resonance Imaging) study of overt picture naming in trilingual participants. In this case, the difference between a high-proficient and a low-proficient further language can be assessed within subjects with no between-group confound. We also used a monolingual group to assess the neural correlates of switching between two categories of response within the same language. We report a novel result: relative language proficiency dissociates response of the pre-SMA/ACC and left caudate during language switching. Switching between languages increased pre-SMA/ACC response regardless of proficiency differences. By contrast, left caudate response did vary with proficiency differences. Switching from the most to the least proficient language increased the response. Within-language switching, as contrasted with between-language switching, elicited a comparable increase in pre-SMA/ACC response but a decrease in left caudate response. Taken together, our data support a wider role of pre-SMA/ACC in task monitoring and establish the critical role of the left caudate in the selection of the less proficient language in language switching.